THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND WORK ENVIRONMENT ON THE PERFORMANCE OF PT EMPLOYEES. PERKEBUNAN NUSANTARA III (PERSERO) KEBUN BANDAR BETSY - Ahmad Fitra; Iskandarini; Sugih Arto Pujangkoro (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The Influence of Leadership Style, Organizational Culture, and Work Environment on Employee Performance at Pt. Perkebunan Nusantara Iii (Persero) Kebun Bandar Betsy. This research was conducted at PT. Perkebunan Nusantara III (Persero) Kebun Bandar Betsy, while the object of research is employees at PT. Perkebunan Nusantara III (Persero) Kebun Bandar Betsy.The population in this study were employees of PT. Perkebunan Nusantara III (Persero) Kebun Bandar Betsy as many as 500 people. The sample in this study was 98 people. With the results, Leadership Style partially influences employee performance at PT Perkebunan Nusantara III (Persero) Kebun Bandar Betsy. Organizational culture partially influences employee performance at PT Perkebunan Nusantara III (Persero) Kebun Bandar Betsy. The work environment partially has no effect on employee performance at PT Perkebunan Nusantara III (Persero) Kebun Bandar Betsy. Leadership Style, Organizational Culture and Work Environment simultaneously influence employee performance at PT Perkebunan Nusantara III (Persero) Kebun Bandar Betsy.